Migration and Enrichment of Arsenic in the Rock-Soil-Crop Plant System in Areas Covered with Black Shale, Korea - Ji-Min Yi; Hyo-Taek Chon; Min Park (The Scientific World Journal)
The Okchon black shale, which is part of the Guryongsan Formation or the Changri Formation of Cambro-Ordovician age in Korea provides a typical example of natural geological materials enriched with potentially toxic elements such as U, V, Mo, As, Se, Cd, and Zn. In this study, the Dukpyung and the Chubu areas were selected to investigate the migration and enrichment of As and other toxic elements in soils and crop plants in areas covered with black shale. Rock and soil samples digested in 4-acid solution (HCl+HNO3+HF+HClO4) were analyzed for As and other heavy metals by ICP-AES and ICP-MS, and plant samples by INAA. Mean concentration of As in Okchon black shale is higher than those of both world average values of shale and black shale. Especially high concentration of 23.2 mg As kg-1 is found in black shale from the Dukpyung area. Mean concentration of As is highly elevated in agricultural soils from the Dukpyung (28.2 mg kg-1) and the Chubu areas (32.6 mg kg-1). As is highly elevated in rice leaves from the Dukpyung (1.14 mg kg-1) and the Chubu areas (1.35 mg kg-1). The biological absorption coefficient (BAC) of As in plant species decreases in the order of rice leaves > corn leaves > red pepper = soybean leaves = sesame leaves > corn stalks > corn grains. This indicates that leafy plants tend to accumulate As from soil to a greater degree than cereal products such as grains.